A Retrospective Evaluation of Bifid Mandibular Canal Prevalence of Southeastern Anatolia Population by Cone-Beam Computed Tomography# - Gunes, Nedim; Guler, Rıdvan; Agin, Hatice Demircan; Dundar, Serkan; Eratilla, Veysel (Cumhuriyet University Faculty of Dentistry, 2022)
Introduction: Bifid mandibular canal (BMC) is often detected incidentally on radiological examination and can be observed in unilateral or bilateral forms. The correct localization of the BMC plays an important role in the prevention of complications such as paresthesia, anesthesia, bleeding, traumatic neuroma, which may occur during or after surgical operations on the mandible such as sagittal split ramus osteotomy, impacted third molar tooth extraction, and dental implant surgery. Objective: This study aims to retrospectively evaluate the prevalence of bifid mandibular canal (BMC) in the Southeastern Anatolian population via Conical Beam Computed Tomography (CBCT). Material and Method: In this retrospective study, CBCT images of 615 patients, who applied to the Department of Oral and Maxillofacial Surgery in the Faculty of Dentistry at Dicle University, Turkey, for various reasons from 2015 to 2020, is evaluated and cases with bifid mandibular canals are examined. The prevalence evaluation is conducted by statistical analyses in terms of sex and laterality. Results: According to the analyses, the BMC prevalence did not constitute a significant difference in terms of the age variable. The incidence of unilateral BMC was higher than bilateral BMC. Additionally, the prevalence of BMC was higher in males compared to. Conclusion: BMC, which can be detected more easily and frequently via CBCT technology, is an anatomical formation that should be taken into account during oral and maxillofacial practices. © 2022. All Rights Reserved.
Keywords: Alveolaris Inferior; Anatomical Variation; Bifid Mandibular Canal; Cone-Beam Computerized Tomography